Texturbestämning genom fält-, pipett- och hydrometermetoder - Lidberg, Linnéa (SLU/Dept. of Soil and Environment, 2009)
Texture is an important soil property and accurate particle size analysis of soil texture is therefore crucial. There are a number of well-established and newly developed methods available for determining soil texture. In order to compare the results of these methods, the differences between them must be determined.